PERAN DAN FUNGSI KERAPATAN ADAT NAGARI ALAM PAUH DUO KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - Asri, Habibul; Oktavia, Dian Anggraini (Pendidikan Sosiologi, 2014)
The background of this study is the change in the setting of a thriving village governance in public life and the things that arise in the implementation of village governance, such as the overlapping functions of existing institutions in villages, lack of harmony in the relationship between the institution and the nagari limitations fiscal capacity and villages. The purpose of this study was to clarify the roles and functions of Kerapan Nagari Alam (KAN) Alam Pauh Duo. Formulation of the problem is how the duties and functions of Indigenous KAN Alam Pauh Â district of South Solok. The theory used in this study is the structural functional theory proposed by Robet K. Merton. This type of research is descriptive qualitative research.The technique of collecting data through observation , in-depth interviews , and study documentation. Based on the results of this study concluded KAN role and function as an institution of social control in kenagarian look no further, the role of KAN has been replaced by other social institutions such as the police, and prosecutors. People who have problems immediately reported to the police station and no longer ask for advice to the prince or to KAN. The role and function of KAN in the village government obscured by Badan Musyawarah (BAMUS). Some of the factors that hinder the role and function of KAN in Nagari Alam Pauh Duo government offices Adat Nagari is still riding in walinagari office, Human Resources is still low, the lack of clarity and determination of the main tasks, and functions, as well as the issue of asset are unclear and uncertain, and the absence of regulation KAN.